The Legislative System of Bangladesh: A Study from Historical Viewpoint - Sikder, Manir Uddin (The Jahangirnagar Review, 2024)
In order to implement the will of the state, the government has to perform mainly three functions namely lawmaking, administration and judicial execution. Governments do these functions with executive, judiciary and legislative branch. The main functions of the Legislature are to make and amend laws, regulate the administration and control the expenditure. The Jatiya Sangsad is main legislative organ of People’s Republic of Bangladesh. Origin of Legislature of Bangladesh has traced back to the eighteenth century. Bangladesh was a part of the then erstwhile Bengal Presidency at that time. There were three independent Presidencies run by a Governor-general: Bengal, Madras and Bombay. The British Government passed various laws at various times with the intention of bringing the people of India into the rule of the British Government and governing them in a better manner. The Indian Council Act of 1861 was the first and most significant pillar of constitutional progress. At this context, the present study will try to explore the answers of some common questions: In what ways do the acts serve as instruments of establishing a representative form of government in British India? What were the contexts and consequences of demand of representative form of government in British India? What were structural variation among all the council acts and role of various constituent assemblies? With all these in mind, the main aim of this paper is to depict the history and evolution of the legislative system in Bangladesh.